The Place of the Employment Court in the New Zealand Judicial Hierarchy - Roth, Paul (Victoria University of Wellington Law Review, 2019)
This article considers the status of the Employment Court and its position in the overall court structure in New Zealand. It examines the issue from both an historical and comparative New Zealand legal perspective.